Growing up ethnic : nationalism and the Bildungsroman in African American and Jewish American fiction - Japtok, Martin (University of Iowa Press, 2005)
Growing Up Ethnic examines the presence of literary similarities between African American and Jewish American coming-of-age stories in the first half of the twentieth century; often these similarities exceed what could be explained by sociohistorical correspondences alone. Martin Japtok argues that these similarities result from the way both African American and Jewish American authors have conceptualized their "ethnic situation." The issue of "race" and its social repercussions certainly defy any easy comparisons. However, the fact that the ethnic situations are far from identical in the case